The Level of Compliance of Muhammadiyah Citizens to The Decision of The Muhammadiyah Central Leadership Number 01/MLM/1.0/E/2024 - Handoko, PUJI (Universitas Syiah Kuala, 2024)
This study aims to examine the level of compliance among Muhammadiyah members in Banjarnegara with the Decree of the Muhammadiyah Central Leadership Number 01/MLM/1.0/E/2024, which establishes the Eid al-Fitr holiday on 1 Shawwal 1445 Hijri, corresponding to April 10, 2024. This research employs a qualitative approach, collecting data from Muhammadiyah branches and sub-branches in Banjarnegara. The data were analyzed using techniques of classification, coding, editing, and interpretation. The results show that all Muhammadiyah members in Banjarnegara (100%) comply with the decree, indicating a high level of adherence to organizational rules. The study also found that Muhammadiyah uses the hisab wujudul hilal method, which combines astronomical calculations and moon sighting, to determine the beginning of the lunar month.